Voortrekker Road – Street Art as an Agency of Change by Bhongiwe Hlekiso - Hlekiso, Bhongiwe (WritingThreeSixty: Journal or Research and Creative Text, 2021)
To me, [street art] is a way to experience the deep soul of urban places, a kind of tribal conscience . . . like going and meeting the people who have really lived the towns. They develop something in their rooms they later bring outside into the streets. In this sense, it may be an experience even more authentic than going to visit the MoMA, where paintings are collected from everywhere. And thus, the fact that the MoMA is there and not in Johannesburg is by chance, it doesn’t change a lot. (Luisa, dweller, Milan)